Pemberdayaan Perempuan: Melalui Ekonomi Kreatif dengan Merajut - Azizah, Siti Shoimatul (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas KH. A. Wahab Hasbullah, 2025)
The women's empowerment program through hand-knitting craft training was chosen because the process is relatively easy, flexible, and affordable. The community service method used a Participatory Action Research (PAR) approach, encouraging active participation from planning to evaluation. The results showed that 20 participants from various women's organizations in Lumajang District successfully mastered basic crochet stitches and produced completed crochet wallets and accessories. The training received positive responses, equipping women with skills to create valuable products for potential entrepreneurship.